Wireless Charging System for Electric Vehicles - Yan, Zheng (International Journal of Mechanical and Electrical Engineering, 2024)
With the popularization of electric vehicles, wireless charging technology has shown significant advantages in charging convenience, security and other aspects, and has become a research hotspot in the field of new energy vehicles. The purpose of this paper is to discuss the principle, architecture, standards, protocols and development trend of the wireless charging system for electric vehicles. This paper expounds the basic concepts and main technical types of wireless charging, and reveals the application of electromagnetic induction and magnetic resonance in wireless charging; The composition and function of the wireless charging system, as well as the key technical challenges in practical application, are analyzed; The mainstream wireless charging standards and the importance of standardization are sorted out; The development direction, external influencing factors and future application scenarios of wireless charging technology are prospected, which provides theoretical basis and practical guidance for further research on wireless charging technology of electric vehicles.